ANALISIS KELEMAHAN BERFIKIR KRITIS SISWA SMK ANNIHAYAH DALAM BERPENDAPAT - Agung Sudibyo (Concept: Journal of Social Humanities and Education, 2022)
School is an element of activity that will accommodate various student characters. One of them is critical thinking. Critical thinking will have an impact on the learning process and the results that will be obtained by students. However, in critical thinking, it has a weakness that becomes something that must be improved. The purpose of this research is to examine the weaknesses of critical thinking of SMK students. The method used is a qualitative approach with descriptive analysis. Data collection techniques using observation and interview techniques. The results of this study are to describe the weaknesses of students in critical thinking